PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN DAN PENERAPAN SISTEM E-FILING TERHADAP KEPATUHAN WAJIB PAJAK PRIBADI DENGAN SOSIALISASI PERPAJAKAN SEBAGAI VARIABEL MODERASI - Khobiru, Humul; Yusuf, Nur’aini (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This research aims to test whether there is an influence between understanding tax regulations and implementing the e-filing system on personal taxpayer compliance with tax socialization as a moderating variable. The population in this study are individual taxpayers at KPP Pratama Pondok Aren. The number of samples in this research was 100 respondents. The sampling method uses the Slovin formula calculation. The research method used is quantitative with the data source in the form of primary data. The data analysis method uses multiple linear regression analysis with SPSS version 26. The results of this research provide empirical evidence that partially the variable understanding tax regulations has a positive effect on taxpayer compliance, while the variable implementing the e-filing system has no effect on taxpayer compliance. Then, the research results also showed that tax socialization was able to moderate the influence of understanding tax regulations on taxpayer compliance, and the research results showed that tax socialization was not able to moderate the influence of implementing the e-filing system on taxpayer compliance.